Gut microbiota-based bioassay for the quality evaluation of different species of Dendrobium and their therapeutic potential in type 2 diabetes - Junju Zou; Qianbo Song; David Tai Wai Lau; Pang Chui Shaw; Zhong Zuo (Chinese Medicine)
Abstract Background Dendrobium (DEN) have been utilized as valuable medicinal resource in China used for millennia for prevention and treatment of various diseases, particularly diabetes via alteration of their disordered gut microbiota. Purpose The current study aimed to differentiate the quality of different species of DEN via an in vitro system including gut microbiota fermentation followed by antioxidative and hypoglycemic bioassays. Material and methods About 100 g fresh DEN from four species (DEN-5 ~ DEN-8) was extracted with 1L boiling water twice with 1 h each time followed by centrifugation to obtain the supernatants as DEN aqueous extract. About 10 mg/mL of each DEN aqueous extract was fermented with fecal fluid from db/db mice for 12, 24 and 48 h, followed by monitoring the changes in total polysaccharide and polyphenol contents, antioxidative, hypoglycemic activities. Additionally, the level of short chain fatty acids and the abundance/diversity of gut microbiota in the DEN fermentation mixture were monitored via GC/MS and 16S rRNA, respectively. Moreover, in vivo hypoglycemic activities of DEN-5 ~ DEN-8 at the dosage of 200 mg/kg once daily for 14 days were also evaluated in db/db mice. Results DEN-5 ~ 8 varied in the content of polysaccharides (0.23–0.61, w/w) and polyphenol (0.008–0.023, w/w). Based on the free radical scavenging percentage, DEN antioxidative activities ranked as DEN-7≈DEN-8 > DEN-5 ≈DEN-6. Based on the percentage of enzyme inhibition, DEN antihyperglycemic activities ranked as DEN-5≈DEN-6 > DEN-8 > DEN-7. Hypoglycemic activities of DEN-5 ~ 8 in db/db mice were in the order of DEN-5≈DEN-6 > DEN-8 > DEN-7. Further correlation analyses of DEN polysaccharides content, DEN polyphenol content, SCFAs formation after in vitro fermentation, antioxidant activities, and hypoglycemic activities found that 1) polysaccharides contents in DEN-5 ~ 8 were positively correlate with total SCFAs generated after the fermentation, α-glucosidase inhibitory capacity, α-amylase inhibitory capacity, and GLP-1 level; 2) polyphenol contents in DEN-5 ~ 8 were positively correlate with ABTS, DPPH, and superoxide anion scavenging capacity. Conclusions Our current study for the first time utilized a novel in vitro system to assess the hypoglycemic effects of different species of DEN and indicated that polysaccharides content in DEN was positively correlated with hypoglycemic effect while polyphenol content in DEN was positively correlated with antioxidant activity. Graphical Abstract